Peningkatan Kemampuan Pemecahan Masalah Matematis Siswa Melalui Pendekatan TaRL Menggunakan Problem-Based Learning - Fitri Fitri; Suciati Suciati; Arief Ertha Kusuma; Herdiansyah Herdiansyah; Yansar Yansar (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research investigates enhancing students' mathematical problem-solving skills through the Teaching at the Right Level (TaRL) approach, utilizing the Problem-Based Learning (PBL) model focused on social arithmetic. The study involved 31 seventh-grade students at SMP Negeri 1 Tarakan during the 2023/2024 academic year and followed the Kemmis & Taggart PTK model, comprising planning, action, observation, and reflection across two cycles. Implementation success criteria were defined as 75% of students scoring ≥ 74. In the first cycle, there was a slight decrease (3%) in students achieving this score; however, the second cycle showed a 12% improvement. Ultimately, 97% of students scored ≥ 74, averaging 91.78. These findings indicate that integrating the TaRL approach with the PBL model effectively enhances the mathematical problem-solving skills of junior high school students in social arithmetic